Zabezpieczanie przepływów pieniężnych dotyczących przyszłych transakcji z wykorzystaniem instrumentów pochodnych w świetle prawa bilansowego i podatkowego - Krzeszowski, Wojciech Dawid (Hedging Future Cash Flow Transactions through Derivatives in the Context of Act on Accountancy and Tax Law, 2006)
A Chief Financial Officer is primarily responsible for securing the financial liquidity and preventing from potential risks that could adversely affect an enterprise's standing. One method is hedging future cash flows through derivatives. The paper is aimed at presenting selected issues of possible methods and accounting for hedging future cash flow transactions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 216-226